The Influence of Training and Infrastructure Facilities on the Performance of State Junior High School Teachers in the City of Padang - Nela Noviarti; Hanif Al Kadri; Irsyad Irsyad; Sulastri Sulastri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Based on pre - survey in field drawn that the performance of state junior high school teachers in the city of Padang is still not optimal. this suspected there is relation with training and facilities. By because that need conducted study to test the truth. This study aims to reveal the influence of training and infrastructure facilities on teacher performance in public junior high schools in Padang City. The hypotheses proposed in this study are: (1) training has an effect on teacher performance, (2) infrastructure has an effect on teacher performance, (3) training and infrastructure in a manner together influences teacher performance. The population in this study is all junior high school teachers in the city of Padang, a total of 1,099 people from 11 districts. The sample study amounted to 63 people taken with technique proportionate stratified random sampling which had previously been carried out by clusters in 1 sub-district, namely West Padang District. The research instrument used is a scale evaluation and scale model questionnaire Likert that has tested its validity and reliability. Research data analyzed with multiple linear regression technique. The results of the data analysis show that: (1) training has a significant effect on teacher performance. This can be seen from the acquisition of t-count (2.645) > t-table (1.670) other than that it has a significant value = 0.005 <0.05, (2) infrastructure has a significant effect on teacher performance. This can be seen from the acquisition of t-count (2.827) > t-table (1.670) besides that it has a significant value = 0.006 <0.05 , (3) there is a significant effect of training and infrastructure together on teacher performance with a level a significant value of 0.000 <0.050 and with an f-count value of 434.822. The level of achievement of the teacher's response to training is in the high category (89.39% of the ideal score), the infrastructure variable is in the good category (84.80% of the ideal score) and the teacher'. The findings above imply that training and infrastructure are two factors that can improve teacher performance, apart from other factors